Investigation of intermediate CAG alleles of the HTT in the general population of Rio de Janeiro, Brazil, in comparison with a sample of Huntington disease‐affected families - Thays A. Apolinário; Iane dos Santos daSilva; Luciana de Andrade Agostinho; Carmen L. A. Paiva (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Huntington disease (HD) (MIM: 143100) is a severe autosomal dominant neurodegenerative disease caused by the expansion of CAG trinucleotides (>35) in the HTT. Objective To investigate the frequency of intermediate CAG alleles (IAs) in individuals residing in Rio de Janeiro city with no familial history of HD (general population, GP) in comparison with a sample of individuals from families presenting with HD who were previously investigated by our group (affected sample, AS). Results The frequency of normal CAG alleles was 96.2%, while that of IAs was 3.6%, and that of reduced penetrance alleles was 0.2% in the GP (n = 470 chromosomes); 7.2% (17/235 individuals) of the GP presented an IA in heterozygosis with a normal allele. There was no statistically significant difference between the frequencies of the IAs in the GP and in the AS (p = .9). The most frequent haplotype per normal allele was (CAG)17‐(CCG)7 (101/461) and per IA was (CAG)27‐(CCG)7 (6/17) in the GP. These haplotypes were also the most frequent in the normal and IA chromosomes of the AS, respectively. Conclusion The genetic profiles of the IAs obtained from GP and AS were rather similar. It is important to investigate the frequencies of the IAs because expansions arise from a step‐by‐step mechanism in which, during intergenerational transmission, large normal alleles can generate IAs, which are then responsible for generating de novo HD mutations. The genetic investigation of IAs in the GP was also important because it was focused on the population of Rio de Janeiro, an understudied group. CCG7 was the most frequent CCG allele in linkage disequilibrium with normal, intermediate, and expanded CAG alleles, similar to the Western Europe population. However, a more robust investigation, in conjunction with haplogroup determination (A, B, or C), will be required to elucidate the ancestral origin of the HTT mutations in Brazilians.